2021
DOI: 10.1007/s13202-021-01132-2
|View full text |Cite
|
Sign up to set email alerts
|

Seismic expression of miocene carbonate platform and reservoir characterization through geophysical approach: application in central Luconia, offshore Malaysia

Abstract: A substantial proportion of proven oil and gas reserves of the world is contained in the carbonate reservoir. It is estimated that about 60% of the world’s oil and 40% of gas reserves are confined in carbonate reservoirs. Exploration and development of hydrocarbons in carbonate reservoirs are much more challenging due to poor seismic imaging and reservoir heterogeneity caused by diagenetic changes. Evaluation of carbonate reservoirs has been a high priority for researchers and geoscientists working in the petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Of the sedimentary rocks, carbonate (limestone and dolomite) holds more than 50%-60% of the conventional oil and gas reservoirs in the sedimentary basins of the world (Rohel, 1985;Kargarpour, 2020;Bashir et al, 2021). However, predicting reservoir quality at an inter-well scale (Lai, 2019), identifying high-permeability zones with high porosity (Choquette and pray, 1970;Bohnsak, 2020), and preparing welldefined reservoir characteristics within petrophysical parameters (Nelson 2001;Lucia 2007) are among the major issues associated with carbonate reservoirs (Kelleys and Wallis 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the sedimentary rocks, carbonate (limestone and dolomite) holds more than 50%-60% of the conventional oil and gas reservoirs in the sedimentary basins of the world (Rohel, 1985;Kargarpour, 2020;Bashir et al, 2021). However, predicting reservoir quality at an inter-well scale (Lai, 2019), identifying high-permeability zones with high porosity (Choquette and pray, 1970;Bohnsak, 2020), and preparing welldefined reservoir characteristics within petrophysical parameters (Nelson 2001;Lucia 2007) are among the major issues associated with carbonate reservoirs (Kelleys and Wallis 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, predicting reservoir quality at an inter-well scale (Lai, 2019), identifying high-permeability zones with high porosity (Choquette and pray, 1970;Bohnsak, 2020), and preparing welldefined reservoir characteristics within petrophysical parameters (Nelson 2001;Lucia 2007) are among the major issues associated with carbonate reservoirs (Kelleys and Wallis 1991). Petrophysical analysis of carbonates is a challenging task: different techniques have been used to determine their petrophysical characteristics (Wang et al, 2016;Bashir et al, 2021;Salifou et al, 2021;Aboubacar et al, 2022). Porosity and permeability are the primary petrophysical parameters that define the reservoir characteristics of sedimentary rock.…”
Section: Introductionmentioning
confidence: 99%
“…Similar resources have also been reported from the Ordovician carbonates of the Ordos and Tarim basins of China (Wei et al, 2017;Chen et al, 2020). Recent studies have also focused on such potential tight carbonates from various parts of the world including offshore Malaysia (Bashir et al, 2021), Pakistan (Ali et al, 2022;Ullah et al, 2022), and China (Jiang et al, 2022). Three recent works by Boutaleb et al (2021), Radwan et al (2021) and Fea et al (2022) reported selfsourcing and self-storing unconventional carbonate intervals from the African continent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, combining sedimentology and diagenesis can help us to understand the diagenetic changes in the exposed rock. The study area, Bintulu, is situated in the NW Sarawak (Hutchison, 1996;Liechti et al, 1960;Bashir et al, 2021). The exposed Nyalau Formation is mainly composed of sandstone, clays, lignite and shales (Madon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%